DETECCIÓN RÁPIDA DE ROTAVIRUS Y CORONAVIRUS EN CRÍAS DE ALPACA (Vicugna pacos) CON DIARREA EN LA REGIÓN DEL CUSCO, PERÚ - López P., Wellington (2011)
Diarrhea is one of the leading causes of alpaca cria mortality in Peru and elsewhere. Defining infectious pathogens involved in morbidity and mortality from diarrhea in crias is of significant importance for its appropriate control. This study reports the detection of rotavirus and coronavirus antigens in feces collected from crias with acute diarrhea and intestinal contents from dead crias. The fecal samples were screened for rotavirus or coronavirus antigens by rapid immunochromatographic methods. Three of the 14 fecal samples were positive for rotavirus antigen while the intestinal contents were all negative. Five of 14 fecal samples were positive for coronavirus and all the intestinal contents were negative. These results suggest that both rotavirus and coronavirus are associated with a proportion of cases of diarrhea in crias but do not rule out the possibility of co-infection with other pathogens. The actual prevalence and impact of these two viruses requires further investigation.